FAKTOR-FAKTOR YANG MEMENGARUHI PENGHINDARAN PAJAK PADA PERUSAHAAN MANUFAKTUR DI BEI - Derianto Yino; Yohanes (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this research is to obtain empirical evidence regarding the effect of profitability, leverage, company size, capital intensity, institutional ownership, sales growth, and audit quality on tax avoidance. Population used in this research are manufacturing companies listed on the Indonesia Stock Exchange during the period 2018 to 2020, using purposive sampling as the sample selection method. There are 186 data from 62 companies that match the research criteria and are analyzed using multiple regression analysis.The results of this study indicates that profitability has an effect on tax avoidance. While it shows different result, such as leverage, company size, capital intensity, institutional ownership, sales growth and audit quality having no effect on tax avoidance. Profitability can affect tax avoidance because of the company preference to be able to obtain maximum income rather than paying the company's tax burden. This research is expected to be able to give implication to the managerial's regarding the policy on asset acquisition, that can be a flaw in the practice of tax avoidance caused by the depreciation of asset that can deduce the tax expense whilst affecting the level of company income. This research have new addition and update such as adding sales growth and audit quality as a variable and the period used for this research is 2018-2020